Effect of ramp slope on intensity thresholds based on correlation properties of heart rate variability during cycling - Fleitas‐Paniagua, Pablo R.; Almeida Azevedo, Rafael; Trpcic, Mackenzie; Murias, Juan M.; Rogers, Bruce (Physiological reports, 2023)
An index of heart rate variability (HRV), detrended fluctuation analysis (DFA a1) has gathered interest as a surrogate marker of exercise intensity boundaries. The aim of this report was to examine heart rate variability threshold (HRVT) behavior across different ramp incremental (RI) slopes. Seventeen participants completed a series of three RI (15, 30, and 45 W · min−1 slopes) with monitoring of gas exchange parameters, heart rate (HR) and HRV. HRVT1 was defined as the V̇O2 or HR at which DFA a1 reached 0.75 and the HRVT2 at which these values reached 0.5. HRVTs were compared by Pearson's r, Bland–Altman analysis, ICC3,1, ANOVA, and paired t‐testing. An excellent degree of reliability was seen across all three ramps, with an ICC3,1 of 0.93 and 0.88 for the HRVT1 V̇O2 and HR, respectively, and 0.90 and 0.92 for the HRVT2 V̇O2 and HR, respectively. Correlations between HRVT1/2 of the individual ramps were high with r values 0.84–0.95 for both HR and V̇O2. Bland–Altman differences ranged between −1.4 and 1.2 mL · kg−1 · min−1 and −2 and +2 bpm. Paired t‐testing showed no mean differences between any HRVT1/2 ramp comparisons. Cycling ramp slope does not appear to affect either HRVT1 or HRVT2 in terms of HR or V̇O2.